Le tourisme est-il aujourd’hui sur une trajectoire de développement durable à la Guadeloupe ? Nécessité de concilier compétitivité, productivité et durabilité - Louis Dupont (Études Caribéennes)
How does one make it possible for tourism to be sustainable in such a way that it can lead to goals of sustainable development? This is a crucial question for all tourist destinations. The purpose of this study is to analyse the main items in this regard also, to assess the viability of tourism sector in Guadeloupe, using several analytic tools such as tourist area cycle model of Butler, DEA model, multicriteria optimization model, and a sustainable performance index for tourism.The results reveal a strong and symbiotic relationship between competitiveness, productivity and sustainability concepts also, low sustainability of tourism in Guadeloupe, a modest contribution of tourism to local economy and employment. At last, a low eco-efficiency index as the result of carbon monoxide.